Konseling Gizi tentang Cegah Anemia Sejak Dini pada Siswa SMP PPTQ Al-Rasyid Sukoharjo: Nutrition Counselling on Early Anaemia Prevention in Junior High School Students at PPTQ Al-Rasyid Sukoharjo - Rahmawaty, Setyaningrum; Maghfiroh, Khoirunnisa' Ramadhan; Fauzan, Saminur; Marzaleva, Valentina Febri; Sari, Silvia Rahma Devita; Efendi, Masyiithoh Ridha; Saputri, Vara Budi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The monitoring results of student’s hemoglobin (Hb) levels in the Tahfid Qur'an Islamic Boarding School (PPTQ) Al-Rasyid Sukoharjo showed a high prevalence of anemia at 63.64%. The intervention carried out by schools to overcome this issue is by providing iron (Fe) tablets, but there have been no nutritional education activities related to anemia. This community service aims to improve students’ knowledge regarding anemia including definition, causes, and prevention through a balanced diet. The service method was carried out through a counseling-based nutrition care process (NCP) approach which begins with pre-test activities and ends with a post-test to determine the increase in student knowledge. A total of 55 students participated in the counseling. The post-test results showed an increase in students' knowledge, from an average initial score of 6.65 to 7.65 (p=0.001).